Pirfenidone in real life: A retrospective observational multicentre study in Italian patients with idiopathic pulmonary fibrosis. (September 2019) - Vancheri, Carlo; Sebastiani, Alfredo; Tomassetti, Sara; Pesci, Alberto; Rogliani, Paola; Tavanti, Laura; Luppi, Fabrizio; Harari, Sergio; Rottoli, Paola; Ghirardini, Alessandra; Kirchgaessler, Klaus-Uwe; Albera, Carlo
Abstract: Rationale: Real-world data on pirfenidone treatment of patients with idiopathic pulmonary fibrosis (IPF) are limited. This study assessed the effectiveness of pirfenidone in a large real-life Italian IPF cohort. Methods: IRENE was an observational, retrospective study of patients with IPF treated with pirfenidone in routine clinical practice (18 centres). At Month 6, a mandatory re-evaluation of forced vital capacity (FVC) decline (absolute change < 10%) was required to continue pirfenidone. The primary effectiveness outcomes were absolute change from baseline in FVC and the percentage of patients with ≥ 10% absolute decline in % predicted FVC at Month 12. Safety was described by adverse event (AE) occurrence. Prespecified subgroups included sex, age, presence/absence of emphysema, usual interstitial pneumonia (UIP) pattern on high-resolution computed tomography, and baseline lung function. Results: The study included 379 patients (mean age, 67.6 years; 78.1% male). Mean change from baseline in FVC and the percentage of patients with ≥ 10% absolute decline in % predicted FVC at Month 12 were −81.8 mL (SD, 419.6 mL; P  = 0.002) and 16.0% (95% CI, 12.2–20.9%), respectively. Disease progression was similar across prespecified subgroups, including patients with definite vs possible UIP. Overall, 211 AEs occurred in 149 patients (39.3%), with serious AEs in 31 patients (8.2%) and 9 discontinuations due to AEs. Skin and gastrointestinal AEs were most frequent. Fifteen patients (4.0%) died. Conclusions: The decline in FVC and the safety profile observed in this real-world IPF cohort were consistent with the findings of the Phase III pirfenidone trials. Highlights: 379 real-world pirfenidone-treated patients with IPF were analysed retrospectively. FVC decline and safety were consistent with Phase III pirfenidone trial results. Results were similar in prespecified subgroups, including definite vs possible UIP.